Analisis Framing Dan Retorika dalam Teks Pidato Menteri Luar Negeri RI Terkait Isu Kemanusiaan di Palestina Tahun 2024 - Raditya Aryasatya Pratama (Journal on Education, 2025)
This study focuses on the analysis of rhetoric and framing in the speeches of the Minister of Foreign Affairs of the Republic of Indonesia, Retno Marsudi, delivered at two major international forums in 2024, namely the United Nations Security Council Open Debate and the International Court of Justice. Using a qualitative approach grounded in the interpretive paradigm, this research employs Ibnu Hamad's framing analysis to understand how the Minister of Foreign Affairs constructs discourse related to humanitarian issues in Palestine. Pathos rhetoric serves as a key element in the speech text, used to evoke the audience's emotions and influence their perception of human rights issues in the Israel-Palestine conflict. The analysis results reveal that Minister Retno Marsudi’s speeches highlight verbal and non-verbal symbols that reinforce Indonesia's solidarity with Palestine. The use of emotional language, quotes from Israeli officials, and symbolic attributes like the keffiyeh support the framing aimed at portraying Israel as the primary perpetrator of humanitarian crimes. Strategic fact presentation is also employed to emphasize the United Nations Security Council's failure to enforce resolutions against Israel. Priming is conducted by selecting critical moments to maximize the audience's attention to the delivered message. This study provides valuable insights into the effectiveness of humanitarian diplomacy through state speeches. However, the effectiveness of the pathos rhetoric used needs further examination by observing the audience's direct responses. This research is expected to contribute to the development of political communication studies, particularly in the context of framing and rhetoric in state speech texts.